Making the ‘rules of the game’: constituting territory and authority in Nicaragua's indigenous communities - Larson, A.M. (2010)
Indigenous communities, particularly in Latin America, are increasingly winning recognition of rights to lands and forests that they have managed or used historically under customary institutions. If property refers to ‘the rules of the game’, this article uses the constitution of indigenous communal territories in Nicaragua to examine the process of ‘making the rules’. Specifically, the recognition of rights by central governments leads to political contestations over both territory and authority as communities and indigenous political leaders vie for different configurations of both lands and new territorial authorities. That is, the process of constituting large collective territories is intimately related to the constitution of authority, as it involves not only the negotiation of physical boundaries but also the recognition of an existing authority structure – or the creation of a new entity – to represent the beneficiaries. In Nicaragua's North Atlantic Autonomous Region, then, the decision over ‘which configuration of territory’ is ultimately a political negotiation over which ‘authority’ will have the right to control and enforce access to which rights and benefits from land and natural resources.